Man Women Relationship In Anitha Desai Novel: Exploring the Dynamics of Man-Woman Relationships in Anita Desai's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Anita Desai is one of the most powerful contemporaryIndian Novelists in English. Her interpretation of man-woman relationship isinfluenced and conditioned by complex social milieu. Mostly woman areculturally as well as emotionally dependent on man and any disruption inrelationship proves to be a loss of self. In this paper we present about man womenrelationship in Anitha Desai novel.